Formação ou auto-heteroecoformação? a capacitação/desenvolvimento tecnológico de professores em uma escola particular - Santos, Cléria Ferreira dos (2022)
This study aims to describe and interpret the phenomenon of teacher technological training provided by a private school, perceived as a phenomenon of human experience. In order to fulfill this purpose, the following research question is considered: What is the nature of teacher technological training provided by a private school? The investigated phenomenon is inferred from the subjects who experienced it, i.e., five in-service basic education teachers, among them the researcher herself, who work in a private school in the city of São Paulo. This study examines teacher technological training under the Complexity approach to observe the self-, hetero-, and eco-articulations in their dimensions, thereby encouraging reflection on training/development workshops aimed at technology training, which is viewed as an important aspect of teacher education. The research is theoretically grounded in the Epistemology of Complexity (Morin 2005, 2010, 2015b, 2016), on Paulo Freire's Pedagogy (1994, 2001, 2004), on the self-hetero-eco technological formation constructs by Freire (2009) and Freire and Leffa (2013), and on the teacher education complex view by Moraes (2007, 2019). The methodological orientation of this qualitative study is guided by the Complex Hermeneutic-Phenomenological Approach, proposed by Freire (2009, 2012, 2017). The description and interpretation of the phenomenon in focus were drawn from textual registers obtained from questionnaires and a reflexive study journal. The phenomenon in focus: teacher technological training provided by a private school, revealed the following complex hermeneutic-phenomenological themes: time, autonomy, support, and engagement